2011
DOI: 10.3390/rs4010001
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving Forest Inventory Variables with Terrestrial Laser Scanning (TLS) in Urban Heterogeneous Forest

Abstract: Abstract:We present the point cloud slicing (PCS) algorithm, to post process point cloud data (PCD) from terrestrial laser scanning (TLS). We then test this tool for forest inventory application in urban heterogeneous forests. The methodology was based on a voxel data structure derived from TLS PCD. We retrieved biophysical tree parameters including diameter at breast height (DBH), tree height, basal area, and volume. Our results showed that TLS-based metrics explained 91.17% (RMSE = 9.1739 cm, p < 0.001) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
122
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 51 publications
2
122
0
1
Order By: Relevance
“…Several studies have shown that TLS is a promising technology because it provides objective measures of tree characteristics including height, plot level volumes, diameter at breast height (DBH), canopy cover, and stem density [12]. However, drawbacks include reduced spatial resolution of the tree surface point cloud with increasing distance to the sensor, and laser pulses are unable to penetrate through occluding vegetation; thus, TLS point density may be insufficient and provide underestimates compared to field-measured estimates [13,14]. However, the modern laser scanners with a sufficiently wide beam, either terrestrials or installed on Unmanned Aerial Vehicles (UAVs) (for example Riegl Vux-1), appear to be very promising.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that TLS is a promising technology because it provides objective measures of tree characteristics including height, plot level volumes, diameter at breast height (DBH), canopy cover, and stem density [12]. However, drawbacks include reduced spatial resolution of the tree surface point cloud with increasing distance to the sensor, and laser pulses are unable to penetrate through occluding vegetation; thus, TLS point density may be insufficient and provide underestimates compared to field-measured estimates [13,14]. However, the modern laser scanners with a sufficiently wide beam, either terrestrials or installed on Unmanned Aerial Vehicles (UAVs) (for example Riegl Vux-1), appear to be very promising.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, LiDAR (Light Detection And Ranging) and especially terrestrial laser scanning (TLS) have been applied to analyze standard tree dendrometrics such as stem position, tree density, DBH, TH, basal area, and wood volume [10][11][12][13]. For example, Hopkinson et al [10] estimated DBH and TH based on TLS data, but still relied on standard allometric equations for wood volume estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Calipers, a device used to measure the distance between two opposite sides, can easily measure the diameter or cross-section of a tree trunk [10]. With advancements in equipment, modern methods of collecting forest inventory data include laser rangefinders [11], terrestrial light detection and ranging (LiDAR; [12,13]), and even smartphone applications [14], which improve efficiency and data quality. Although different methods can be used to collect forest data depending on various technologies and their suitability, the methods must always be used on the ground.…”
Section: Introductionmentioning
confidence: 99%